The use of a simple and affordable skin patch for measurement of transcutaneous bilirubin levels in neonates during phototherapy - Kallimath, Aditya; Patnaik, Suprabha; Suryawanshi, Pradeep; Deshmukh, Rupeshkumar; Malshe, Nandini (Frontiers in Pediatrics, 2024)
Transcutaneous bilirubin (TcB) measurements during and after phototherapy for hyperbilirubinemia must be performed on unexposed skin. There are commercially made skin patches for this purpose but they are relatively unavailable in low-resource settings. We devised a simple cotton patch and tested its use for TcB during phototherapy.Measurements were taken in healthy neonates born at ≥ 35 weeks gestational age who were undergoing phototherapy for hyperbilirubinemia in western India before, 12 hours after the start, and 12 hours after the end of phototherapy. Serum bilirubin (TSB) was measured by the diazo method in the clinical laboratory. TcB measurements were performed using a Dräger Jaundice Meter JM-105 placed over the sternum on two skin areas that were protected during and after treatment by a commercial (Philips BilEclipse) or self-made patch comprised of cotton gauze and wool.Forty-seven neonates were included in our study. Before phototherapy, TSB and TcB values had a strong correlation (Pearson, r = 0.88), with a mean difference of -1.35 mg/dL. Correlations with TSB were good and equivalent for TcB values measured in skin covered by the commercial and self-made patches, during (0.78 and 0.70, respectively) and after (0.57 and 0.58, respectively) phototherapy. TcB values taken on skin covered by the two patches correlated well both during and after phototherapy, with r = 0.82 and 0.90 respectively, and mean (95% CI) differences of -1.21 and -0.32 mg/dL, respectively.Reliable TcB measurements taken during and after phototherapy can be achieved on skin covered with a simple and affordable cotton skin patch.